Obspack CO time-series result from Svartberget (35.0 m) - Eric Larmanou; Per Marklund; Mikaell Ottosson-Löfvenius; Paul Smith; ICOS RI (Integrated Carbon Observation System, 2025)
This data file contains high accuracy European ObsPack observational timeseries in netCDF format of ambient mole fraction of co in dry air collected at Svartberget (35.0 m). The measurements were calibrated using the WMO GAW calibration scale WMO X2014A. Included are (all whenever available) historical PI QCed data, ICOS Level 2 data, ICOS FastTrack data and ICOS NRT data. It is part of the 2025.3 FastTrack update of the Globalview EU CO data product and is intended for use in carbon cycle inverse modeling, model evaluation, and satellite validation studies. Metadata for the full co product release are available at https://commons.datacite.org/doi.org/10.18160/ZHZF-KXCQ. Please also visit http://www.gml.noaa.gov/ccgg/obspack/ for more information. If you use these data in your research, please consider citing the full ObsPack release that this file is part of (https://commons.datacite.org/doi.org/10.18160/46ST-DEVK).
ICOS RI, Larmanou, E., Marklund, P., Ottosson-Löfvenius, M., Smith, P. (2025). Obspack CO time-series result from Svartberget (35.0 m), 2017-06-01–2025-10-02, European ObsPack, https://hdl.handle.net/11676/3Rv1uSN90gQIsDKG1sR0OjP6
Keywords: Carbon Portal; CO; ICOS; Obspack; WMO X2014A; atmospheric dry air co mole fraction; time series; time instant, UTC; time instant, UTC; quality flag; quality flag; data level (Obspack); data level (Obspack); standard deviation of gas mole fraction; standard deviation of gas mole fraction; ICOS mole fraction uncertainty metrics; ICOS mole fraction uncertainty metrics; CO (dry air mole fraction); CO (dry air mole fraction); Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap